Epistemologi Pendidikan Islam Dan Barat - Muhammad Syaikhon (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Epistemology which is also called the Theory of Science occupies a very urgent space in the development of the progress of a nation's culture or civilization. Epithemology is a branch of philosophy that discusses the nature, source, structure, method and validity of knowledge. The nature of education is all the adult efforts in association with children to lead their physical and spiritual development toward maturity. Adults do not mean just physical maturity but can also mean psychic maturity. The source of Islamic education is revelation (God) and is obtained through a number of channels, healthy senses, correct reports based on authority, sound reason and intuition, while the source of Western education is ratio and experience. Islamic education develops an integral view of the profane and the sacred, while Western education only develops the profane aspect only. Islamic education develops all aspects of the human personality from the heart to the intellect, while Western education is only mindful.